The genome sequence of the eyed flat-backed millipede, Nanogona polydesmoides (Leach, 1814) [version 1; peer review: 2 approved] - Olga Sivell; Duncan Sivell; Gregory D. Edgecombe; Richard J. Twitchett; Christian Owen (Wellcome Open Research)
We present a genome assembly from a specimen of Nanogona polydesmoides (eyed flat-backed millipede; Arthropoda; Diplopoda; Chordeumatida; Craspedosomatidae). The genome sequence has a total length of 406.26 megabases. Most of the assembly (95.49%) is scaffolded into 16 chromosomal pseudomolecules. The mitochondrial genome has also been assembled, with a length of 16.55 kilobases.